2018
DOI: 10.1101/383448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-27a is a key modulator of cholesterol biosynthesis

Abstract: Hypercholesterolemia is a strong predictor of cardiovascular diseases. 3-Hydroxy-3-methylglutaryl-coenzyme A reductase gene (Hmgcr) coding for the rate-limiting enzyme in the cholesterol biosynthesis pathway is a crucial regulator of plasma cholesterol levels. However, the post-transcriptional regulation of Hmgcr remains poorly understood. The main objective of this study was to explore the role of miRNAs in the regulation of Hmgcr expression.Systematic in silico predictions and experimental analyses reveal th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Other miRNAs implicated in potential therapy of hypercholesterolemia are miR-27a and miR-30c. First of them was injected via tail vein into Apoe-/- mice subjected to high cholesterol diet and suggested to diminish plasma lipid levels along with hepatic levels of HMGCR [ 334 ]. Further, miR-27a was proved to directly target HMGCR via translational repression and mRNA decay.…”
Section: Overview Of Mirnas—the Focus On Interplay With Oxidative mentioning
confidence: 99%
See 1 more Smart Citation
“…Other miRNAs implicated in potential therapy of hypercholesterolemia are miR-27a and miR-30c. First of them was injected via tail vein into Apoe-/- mice subjected to high cholesterol diet and suggested to diminish plasma lipid levels along with hepatic levels of HMGCR [ 334 ]. Further, miR-27a was proved to directly target HMGCR via translational repression and mRNA decay.…”
Section: Overview Of Mirnas—the Focus On Interplay With Oxidative mentioning
confidence: 99%
“…Moreover, it was observed that hypoxia, a sign of liver damage, induced binding of early growth response protein 1 (Egr1) to promoter regions of miR-27a, leading to its induction, to mediate the downregulation of HMGCR. Finally, increase of miR-27a and decrease of HMGCR were found in livers of three mice models of MetS [ 334 ]. Further, C57BL/6J mice with diet-induced hypercholesterolemia showed also amelioration of hypercholesterolemia, yet upon delivery of miR-30c mimic to the liver due to decrease of hepatic lipoprotein production but not LDL clearance [ 335 ].…”
Section: Overview Of Mirnas—the Focus On Interplay With Oxidative mentioning
confidence: 99%
“…Doxorubicin treatment in breast cancer was reported to increase levels of intracellular cholesterol [ 21 ]. Chemotherapy resistant leukaemia cells down-regulate miR-27a expression which was known as a key regulator of cholesterol homoeostasis [ 22 , 23 ]. Metabolism of intracellular cholesterol is tightly regulated by complex multi-step networks.…”
Section: Discussionmentioning
confidence: 99%
“…These cell-derived exosomes contain numerous miRNAs, which can be taken up into neighboring or distant cell types including hepatocytes to modulate their function [ 73 ]. Moreover, previous studies demonstrated that miR-27a can interacts with the HMG-CoA reductase 3′ untranslated region in murine and human hepatocytes and downregulate its expression [ 74 ]. Therefore, we believe that the miR-27a within the exosomes presumably secreted from TTP deficient bone marrow derived macrophages as the exosome dock on the hepatocyte modulate the hepatocyte lipid metabolism and downregulate the HMG-CoA reductase mRNA.…”
Section: Discussionmentioning
confidence: 99%